Local Wisdom-Based Policy Innovation in Indonesia During 2018-2021 - Suranto, Suranto; Darumurti, Awang (Universitas Muhammadiyah Yogyakarta, 2024)
This study seeks to identify innovative models of local wisdom-based public services in Indonesia, addressing the gaps in previous research that primarily provided broad descriptions of inclusive public services. Employing a descriptive-exploratory approach, the research utilized an archival method that focused on secondary data. The findings revealed several key insights: (1) Local governments were more active in proposing policy innovations rooted in local wisdom compared to the central government, owing to their closer proximity to service delivery sites; (2) service innovations were predominantly product-oriented, driven by urgent and critical needs; (3) problem-solving innovations were highly prevalent, effectively addressing critical service issues while minimizing cultural clashes; (4) sectors such as education, community empowerment, food security, environmental preservation, and health significantly influenced policy innovations, acting as a bridge between basic community services and local cultural practices; and (5) a dynamic competition emerged between innovators from Java and those outside it, with the latter excelling in the quantity of organizations and local communities, while Java demonstrated superior human resources and infrastructure. The study's novelty lies in its specific focus on the interplay between local wisdom and service delivery in various sectors, providing empirical evidence on how cultural contexts shape policy innovations. This research contributes to the field by offering a nuanced understanding of how local wisdom informs public service innovation, highlighting the importance of localized approaches in service delivery and advocating for the integration of cultural context in public policy development.